Peningkatan Daya Inovatif Pustakawan Melalui Repacking Information Isi Intelektual Koleksi - RIZKI NURISLAMININGSIH (S1 Ilmu Perpustakaan dan Informasi Islam FTK UIN Antasari Banjarmasin, 2019)
ABSTRACTCreativity librarians as a conduit of information officers need to be increased in order to later be able to provide the best possible information to patrons. One of the activities that can be done is repackaging intellectual content collections. These activities are not only limited change the packaging of information from print to electronic form, but also summarize the information content of the collections become more easily understood information. Librarians can learn from the activities of repackaging information in the library of and then modified packaging adapted to fit the needs of information patrons.Keyword: repacking information, innovation, librarian ABSTRAKKreativitas pustakawan sebagai pihak yang bertugas memenuhi kebutuhan informasi perlu terus ditingkatkan. Salah satu kegiatan yang dapat dilakukan adalah kemas ulang informasi. Aktivitas tersebut tidak hanya sebatas pada mengalih media kertas ke elektronik, tetapi juga mencarikan isi intelektual koleksi agar lebih mudah dipahami pemustaka. Pustakawan dapat belajar kemas ulang informasi di perpustakaan LIPI dan kemudian dimodifikasi dan dibuat kedalam bentuk baru sesuai kebutuhan pemustaka.Kata Kunci: Repacking Information, Inovasi, Pustakawan